Svetovalno delo v vrtcu kot podpora ustvarjanju čustveno varnega, socialno vključujočega in spoznavno spodbudnega okolja za otroke - Marjanovič Umek, Ljubica (Šolsko svetovalno delo, 2021)
The article begins by placing kindergarten counseling in a wider theoretical framework, especially sociocultural theories, which lays in the basis for understanding the diverse, interconnected and highly professional activities performed by kindergarten counselors with the purpose of providing added value to the quality of preschool education. Next, it analyses the meaning and role of the counseling work in certain selected areas of the child's development and learning in kindergarten by describing the systemic, preventive and developmental aspects of the activities and work with different target groups, such as children, teachers, heads and parents. A particular focus is also on the necessity of providing adequate systemic and normative conditions fort he quality of kindergarten counselors professional work.
Keywords: otroci; otroški vrtci; predšolska vzgoja; sociokulturne teorije; svetovalni delavci; svetovanje